ЗАСАГЛАЛ ХУВААХ ОНОЛЫН ХӨГЖИЛ, ХАНДЛАГА - С.ЗҮЛЬФИКАР (Politology, 2023)
In this article I have supposed to define and discuss theoretical development of separation of powers in check and balance system as much as acceptance of the system in different liberal democracy and countries. The term separation of power is a model for the governance of a state. The model was first developed in ancient Greece and came into widespread use by the Roman Republic as part of the unmodified Constitution of the Roman Republic. The term is ascribed to French enlightenment political philosopher Baron de Montesquieu. He describe division of power among an executive, a legislature and a separation. In democratic system of governance, a continuum exists between "government" and "parliamentary government". There is actual discussion that "Separation of powers" is feature more inherent to presidential systems. Whereas "fusion of powers" is considered characteristic of parliamentary ones.